A macroeconometric disequilibrium analysis of current and future migration from Eastern Europe into West Germany - Wolfgang Franz; Ursula Oser; Peter Winker (Universität Konstanz, Forschungsschwerpunkt Internationale Arbeitsmarktforschung, 1993)
This paper attempts to evaluate the impact of current and future immigration flows on major macroeconomic variables of the West German economy. The analysis is based on a macroeconometric disequilibrium model for the West German economy. This model is extended until 1995 and used for several simulation experiments. Special attention is given to the notion that the effects of immigration are regime-specific, i.e., they depend on the type of disequilibrium prevailing on the goods and labor market.
Keywords: 330